Дія кремнієво-калійного добрива Аgroglass stimul на проростання пшениці озимої в умовах водного дефіциту - Колесніков, Максим Олександрович; Колесников, Максим Александрович; Kolesnikov, Maksym; Пащенко, Юлія Петрівна; Пащенко, Юлия Петровна; Paschenko, Yuliia (My University, 2018)
UK: Суттєве гальмування ростових процесів та втрати врожаю сільськогосподарських культур в світі відбуваються з причини посух. Використання біопрепаратів та комплексних добрив підвищує стійкість культур до абіотичних стресів та є перспективним. Відомо, що сполуки кремнію посилюють резистентність зернових культур до низки несприятливих факторів довкілля. Висвітлено питання впливу кремнієво-калійного добрива на проростання насіння та мор- фометричні показники проростків пшениці озимої в умовах водного дефіциту. Дослідження проводили з використанням насіння пшениці озимої сорту Антонівка. Для передпосівної обробки насіння використовували добриво Agroglass Stimul в концентраціях 5, 15, ЗО, 60 мл/л. Встановлено, що добриво Agroglass Stimul у концентрації 5-15 мл/л збільшувало схожість насіння пшениці озимої на 5-6 %, виступаючи регулятором осмотичного тиску в тканинах рослин. В умовах водного стресу Agroglass Stimul в усіх досліджуваних концентраціях привело до збільшення сирої маси проростків максимально на 26,6 % та коренів пшениці на 27,4 %. Суха маса проростків перевищувала контрольні значення на 16,5 %, а коренів - на 69,1 % за дії добрива в концентраціях 5-30 мл/л. Найбільш ефективно збільшував довжину проростків пшениці за умов водного дефіциту Agroglass Stimul в концентраціях від 5 до ЗО мл/л. Встановлено, що кремнієво-калійне добриво посилювало ростові процеси, нівелюючи негативний ефект водної депресії. Отримані дані підтверджують результати позитивного впливу кремнієво-калійних добрив на формування продуктивності зернових культур, що вказує на перспективність їх подальшого дослідження. RU: Существенное торможение ростовых процессов и потери урожая сельскохозяйственных культур в мире происходят по причине засухи. Использование биопрепаратов и комплексных удобрений повышает устойчивость культур к абиотическим стрессам и является перспективным. Известно, что кремний усиливает резистентность зерновых культур к ряду неблагоприятных факторов окружающей среды. В статье освещены вопросы влияния кремниево- калийною удобрения па прорастание семян и морфометрические показатели проростков пшеницы озимой в условиях водного дефицита. Исследования проводились с использованием семян пшеницы озимой сорта Антоновка. Для предпосевной обработки семян использовали удобрение Agroglass Stimul в концентрациях 5, 15, 30, 60 мл/ л. Установлено, что удобрение Agroglass Stimul в концентрации 5-15 мл/л увеличивало всхожесть семян пшеницы озимой на 5-6 %, выступая регулятором осмотического давления в тканях растений. В условиях водного стресса Agroglass Stimul во всех исследуемых концентрациях вызвал увеличение сырой массы проростков максимально на 26,6 % и корней пшеницы на 27,4 %. Сухая масса проростков превышала контрольные значения на 16,5 %, а корней - на 69,1 % под воздействием удобрения в концентрациях 5-30 мл/л. Наиболее эффективно увеличивал длину ростков пшеницы в условиях водного дефицита Agroglass Stimul в концентрациях от 5 до 30 мл/л. Установлено, что кремниево-калийное удобрение усиливало ростовые процессы, нивелируя негативный эффект водной депрессии. Полученные данные подтверждают результаты положительного влияния кремний-калийных удобрений на формирование продуктивности зерновых культур, что указывает на перспективность их дальнейшего исследования. EN: Winter wheat relates to the leading grain-forage crops in Ukraine and occupies about 60% of sown area at steppe region. The water deficit has negative impact on winter wheat growth, development and productivity. Significant phisiological and biochemical changes occur in a plant in the course of its adaptation to water stress. The solving of the problem of plants resistance to stress and increasing their productivity is a priority research area in agriculture. One of the possible ways to activate growth processes and raise the genetic potential of plants is using biostimulants and complex fertilizers. The silicum-potassium fertilizers have been widely introduced lately due to their multifunctional properties. However, the agrobiological effect of this fertilizers on crops has not been studied properly. Positive effect of silicic fertilizers was revealed on wheat, barley, rice, sorgum, corn, sunflower, beans, vegetables and citrus crops. Silicum can stimulate plant natural protection reactions through participating in the methabolism. It is proved, that silicum nutriets optimization results in the roots weight and volume increase and improves root’s respiration. The assimilation of micro- and macronutrients raises under the silicon effect. The soluble forms of silicum-potassium fertilizers increase leaf surface of grain crop, activate photosynthetic apparatus, increase the number of productive spikes under drought. The study aim was to determine the influence of silicum-potassium fertilizer «Agroglass Stimul» on germination of the winter wheat under condition of water deficiency. Seeds of Antonovka variety winter wheat were used for the laboratory study. The control variant seeds were soaked in distillated water for 4-6 hours. The experimental variants seeds were soaked in solutions of silicum-potassium fertilizer «Agroglass Stimul» (5, 15, 30, 60, 100 ml/1) at 22+2 °С. Silicum-potassium fertilizer «Agroglass Stimul» was prodused by “PCC Ukrsilikat” (Zaporizhzhia city) with content of Si02-21,3 % and K20-8,3 %. Seeds were germinated for 8 days according to the international protocols. Seeds were grown at 5 % solution of PEG-6000 for water deficiency stress induction. The laboratory germination, length and weight of seedlings and roots of wheat were determined in the course of the experiment. The results were processed statistically. Germination of wheat seeds on 5 % solution of osmotic compound polyetheleneglycol (PEG-6000) create the condition of water deficiency and caused germination decrease of by 9 %. Seed pre-sowing treatment with «Agroglass Stimul» solutions (5-15 ml/1) leveled the negative effect of water depression which indicates germination energy increase by 3.8-5.3 % and laboratory germination of wheat seeds increase by 3.8- 6.0 % to the control index. However, high concentration of fertilizer (60ml/l) inhibited germination of wheat seeds under the condition of water deficiency. The incubation of wheat plants on PEG 6000 solution for 8 days resulted in the essential decrease of both seedlings raw weight by 1.7 times and roots - by 1.43 times compared with the crops grown in water medium. Silicum-potassium fertilizer «Agroglass Stimul» raise the raw weight of wheat seedlings by 5.7 %-26.6 % and root by 17.5 %-27.4 %, respectively, in comparison with untreated seeds. When determining the dry mass it was established that «Agroglass Stimul» fertilizer provided the accumulation of mineral part of the biomass under water stress condition. Similar results were obtained on winter wheat seedlings under condition of salt stress model. The dry weight of seedlings exceeded the control by 12.6 %-16.5 % and roots dry weight by 34.5-69.1 % under the influence of fertilizer in concentration of 5 ml/1-30 ml/1. It is necessary to mention, that even maximum concentration of «Agroglass Stimul» (60 ml/1) didn’t show negative affect under water deficiency conditions, but, on the contrary, it stimulated the accumulation of wheat biomass on the early stage of development. Inadequate water supply is known to inhibit the processes of cells elongation are inhibited which causes stunted plant. Nevertheless, «Agroglass Stimul» promoted seedlings elongation by 13-14 % and roots elongation by 16-30 % compared with the control plants and in a case of pre-sowing seeds treatment. The fertilizer concentration of 5-30 ml/1 increased the length of wheat seedlings the most effectively under water deficiency condition. Thus, silicum-potassium fertilizer «Agroglass Stimul» indirectly influences crop water balance normalization through regulating cells osmotic penetration. Seeds pre-sowing treatment with «Agroglass Stimul» (5-15 ml/1) levels the negative effect of water depression, which indicates wheat’s seeds energy growth and laboratory germination by 5-6 %. It was established that silicum-potassium fertilizer, being as a regulator of osmotic pressure of plant tissues, enhanced growth processes in water stress condition under all studied concentration range (5-60 ml/1).
Действие кремний-калийного удобрения Agroglass Stimul на прорастание пшеницы озимой в условиях водного дефицита
The effect of of silicum-potassium fertilizer «Agroglass stimul» on winter wheat germination under water deficiency
Keywords: пшениця озима; водний дефіцит; кремнієво-калійне добриво; ріст; розвиток; схожість; пшеница озимая; водный дефицит; кремний-калийное удобрение; рост; развитие; всхожесть; winter wheat; water stress; silicum-potassium fertilizer; growth; development; germination